1981
DOI: 10.1111/j.1365-2478.1981.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Zero Memory Non‐linear Deconvolution*

Abstract: A type of iterative deconvolution that extracts the source waveform and reflectivity from a seismogram through the use of zero memory, non-linear estimators of reflection coefficient amplitnde is developed. Here, we present a theory for iterative deconvolution that is based upon the specification of a stochastic model describing reflectivity. The resulting parametric algorithm deconvolves the seismogram by forcing a filtered version of the seismogram to resemble an estimated reflection coefficient sequence. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 6 publications
0
49
0
1
Order By: Relevance
“…The set of equation (6) can be solved using the iterative procedure (GODFREY and ROCCA, 1981). At each iteration, the energy of the estimated signal must be normalized to a fixed value and then the signal model is updated.…”
Section: Methodsmentioning
confidence: 99%
“…The set of equation (6) can be solved using the iterative procedure (GODFREY and ROCCA, 1981). At each iteration, the energy of the estimated signal must be normalized to a fixed value and then the signal model is updated.…”
Section: Methodsmentioning
confidence: 99%
“…As already was noted in [20,58], the described model for the convolutional noise p[n] is applicable during the latter stages of the process, where the process is close to optimality [38]. According to [38], in the early stages of the iterative deconvolution process, the ISI is typically large with the result that the data sequence and the convolutional noise are strongly correlated, and the convolutional noise sequence is more uniform than Gaussian [59]. However, satisfying equalization performance was obtained by [51] and others [20] in spite of the fact that the described model for the convolutional noise p[n] was used.…”
Section: The New Lagrange Multipliersmentioning
confidence: 99%
“…It has been observed that in many geophysical contexts the observed data (the x t 's) are distinctly nonGaussian and a basic object is to deconvolve, estimating the a/s and v/s in the process. A discussion of related questions in the geophysical context can be found in Donoho (1981), Godfrey and Rocca (1981), and Wiggins (1978).…”
Section: Introductionmentioning
confidence: 99%